Contaminants bioaccumulation and pathological assessment in Mytilus galloprovincialis in coastal waters facing the brownfield site of Bagnoli, Italy. (March 2019) - Arienzo, Michele; Toscanesi, Maria; Trifuoggi, Marco; Ferrara, Luciano; Stanislao, Corrado; Donadio, Carlo; Grazia, Villari; Gionata, De Vico; Carella, Francesca
Abstract: We studied the bioaccumulation of metals and PAHs, the pathological conditions, regressive phenomena and pathogens in wild Mytilus galloprovincialis taken along the North Pier facing the former second Italian largest steelworks of Bagnoli. There was no Cd and Pb bioaccumulation with respect to the EU role 221/2002. Metal shell index decreased as follows: Pb > Ni > Zn > Cu and correlates with the pollution state. The level of BaP was up to thirtysixfold higher the EU rule 835/2011. The sum of 4 hydrocarbons, PAH4, were up to seventeen-fold the rule. PAH levels increased toward the coast. Prevalence values of tissue necrosis and inflammatory lesions were between 50 and 100%. In May animals showed lesion like granulocytomas and inflammatory capsules. Signs of atresia, necrotic oocytes and diffused cases of hermaphroditism were detected. An appropriate localization of farming to avoid contamination from sediment turbulence and risks for consumer health is needed. Highlights: Mapping of polycyclic aromatic hydrocarbons and sources in the Gulf of Pozzuoli Twelve diagnostic indexes for attribution of PAHs emission source Determination of sedimentary transit axes along the seabed by grain size analysis Outstanding levels of PAHs pollution over all the Bay of Pozzuoli Pyrogenic nature of PAHs from Bagnoli brownfield through all Pozzuoli Gul